2016
DOI: 10.1021/jacs.6b07882
|View full text |Cite
|
Sign up to set email alerts
|

A Biradical Balancing Act: Redox Amphoterism in a Diindenoanthracene Derivative Results from Quinoidal Acceptor and Aromatic Donor Motifs

Abstract: The reduced and oxidized states of an open-shell diindeno[b,i]anthracene (DIAn) derivative have been investigated by experimental and theoretical techniques. As a result of moderate biradical character and the ability of cyclopenta-fused scaffolds to stabilize both positive and negative charges, DIAn exhibits rich redox chemistry with four observable and isolable charged states. Structural and electronic properties of the DIAn system are brought to light by UV-vis-NIR and Raman spectroelectrochemical measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 43 publications
6
46
0
Order By: Relevance
“…Since the discovery of the first biradicaloid polycyclic aromatic hydrocarbon (PAH) by Tschitschibabin in 1907, the interest in organic open shell π‐conjugated compounds has increased tremendously due to their unique optical, electronic and magnetic properties . Usually, open‐shell PAHs exhibit redox amphoterism, comparatively small HOMO–LUMO energy gaps, enhanced second hyperpolarizability and large two‐photon absorption cross‐sections which makes them interesting for the development of new ambipolar field‐effect transistors, second generation solar cells based on singlet fission, non‐linear optics, energy storage or electronic devices as well as for organic spintronics . Generally, the degree of biradical character y can range from zero (completely closed‐shell) to one (completely open‐shell) with overall spin angular momenta of S= 0 for singlet and S= 1 for triplet states which can be predicted by applying Ovchinnikov's parity model .…”
Section: Methodsmentioning
confidence: 99%
“…Since the discovery of the first biradicaloid polycyclic aromatic hydrocarbon (PAH) by Tschitschibabin in 1907, the interest in organic open shell π‐conjugated compounds has increased tremendously due to their unique optical, electronic and magnetic properties . Usually, open‐shell PAHs exhibit redox amphoterism, comparatively small HOMO–LUMO energy gaps, enhanced second hyperpolarizability and large two‐photon absorption cross‐sections which makes them interesting for the development of new ambipolar field‐effect transistors, second generation solar cells based on singlet fission, non‐linear optics, energy storage or electronic devices as well as for organic spintronics . Generally, the degree of biradical character y can range from zero (completely closed‐shell) to one (completely open‐shell) with overall spin angular momenta of S= 0 for singlet and S= 1 for triplet states which can be predicted by applying Ovchinnikov's parity model .…”
Section: Methodsmentioning
confidence: 99%
“…Recently the synthesis and study of diradical compounds has garnered renewed attention as these species could be useful as promising materials in molecular spintronics, nonlinear optics, and singlet fission . The contribution of the open‐shell form to the ground‐state structure is described by the diradical character index, y , with y= 1 defining a pure open‐shell (OS) system and y= 0 describing a pure closed‐shell (CS) system ,. With the potential to re‐aromatize the quinoidal motif (e.g., 1 , 1′′ ) to a diradical structure (e.g., 1′ ), IFs make an interesting case study.…”
Section: Figurementioning
confidence: 99%
“…Unfortunately, attempts to form single crystals for definitive structural proof were fruitless. However, prior studies have shown that IF derivatives can be reduced easily to monoanion and dianion states to secure crystallographic data ,. Importantly, such reductions do not alter the carbon skeleton, and therefore X‐ray crystallography of the reduced product would reveal the molecule's carbon connectivity and provide the structural confirmation that 6 is the missing IF regioisomer.…”
Section: Figurementioning
confidence: 99%
“…Simple biradicaloid structures, such as 1 itself, 4 tend to be unstable under ambient conditions, and extensive effort has been given to developing chemically robust open-shell systems. The diindeno[1,2-b:1 0 ,2 0 -i]anthracene (DIAn) derivative 3, reported recently by Haley et al 5,6 exem-plies key strategies used to stabilize p-biradicaloids, namely extended ring fusion, steric blocking, and the use of conjugated substituents, such as ethynyl groups. 3 represents the family of stabilized diindenoarene biradicaloids, [7][8][9] which comprises indenouorenes [10][11][12][13][14] and their larger congeners, e.g.…”
Section: Introductionmentioning
confidence: 99%